The Muses Do Not Fall Silent! (Art in Times of War) - Tkachenko, Maryna; Sokolova, Alla; Yuryeva, Kateryna (International Scientific Conference “EDUCATION, RESEARCH, PRACTICE” Proceedings, 2024)
The relevance of this research is driven by the need to refute the well-known Roman saying "Inter arma silent Musae", more familiar to us in its altered form: "When cannons speak, the muses fall silent". In the harsh times of war, art not only must not remain silent but must also help, console, inspire, unite, and provide hope and confidence in victory. The aim of this research is to review and summarize the creative artistic and scientific achievements of the faculty and students of the Faculty of Arts at H.S. Skovoroda Kharkiv National Pedagogical University during the full-scale military aggression of Russia against Ukraine. The research methodology includes cataloging, socio-artistic and pedagogical analysis of the creativity of faculty and students; analysis of the programs of scientific events and lists of publications; conversations and interviews with authors and participants of artistic and scientific events. The research results showed that since February 2022, a significant number of artistic works (paintings, murals, choreographic compositions, choral arrangements, etc.) and scientific works (articles, monographs, etc.) have emerged. Numerous scientific and practical events have been held, and faculty and students have participated in a significant number of national and international artistic festivals and competitions. The conclusions allow us to assert that Ukrainian muses not only refused to remain silent but also raised their voices against war and aggression, in defense of Ukraine's independence and territorial integrity, its culture, and artistic heritage.